Transcriptomic and metabolomic analyses provide insights into the attenuation of neuroinflammation by nervonic acid in MPTP-stimulated PD model mice. Issue 1 (9th December 2022) - Wang, Xueqi; Zhu, Xinliang; Li, Xu; Li, Zhengdou; Mao, Ying; Zhang, Shunbin; Liu, Xiaoxiao; Liu, Xingguo; Liu, Yapeng; Cao, Fuliang; Zhang, Ji
Abstract : Nervonic acid is one of the most promising bioactive fatty acids, which is believed to be beneficial for the recovery of human cognitive disorders. Abstract : Nervonic acid is one of the most promising bioactive fatty acids, which is believed to be beneficial for the recovery of human cognitive disorders. However, the detailed neuroprotective effects and mode of action of nervonic acid have not yet been fully elucidated. In this study, we used an MPTP-stimulated mouse Parkinson's disease (PD) model as a target to investigate the neuroprotective effects by behavioral tests and integrative analysis of trancriptomes and metabolomes of PD mouse brain with nervonic acid injections. The KEGG pathway enrichment analysis of transcriptomes showed that the genes involved in neuroinflammation were significantly increased after MPTP induction and have been greatly inhibited by nervonic acid injection, while nervonic acid also greatly improved nerve growth and synaptic plasticity pathways which were significantly downregulated by MPTP. At the same time, the upregulation of oleic acid and arachidonic acid metabolism pathways and the downregulation of amino acid metabolism pathways in metabolomes were particularly highlighted in the nervonic acid protection groups compared with the PD model. Meanwhile, it was found that arachidonic acid, oleic acid and taurine play an important regulatory role in the neuroprotective mechanism of nervonic acid through fatty acid metabolism by integrative analysis. Therefore, our study laid a solid foundation for further studies on the specific role of nervonic acid in the inhibition of PD at the level of metabolic regulation.